A Decision Procedure for Capital Rationing Investment and Borrowing Decisions - Lohmann, Jack R.; Oakford, R. V. (The Engineering economist, 1980)
This paper presents a decision procedure to aid in making capital rationing investment and borrowing decisions. Weingartner's Basic Horizon Model and Oakford and huesen's Maximum Prospective Value criterion are both extended to explicitly include long-term borrowing decisions. Information derived from interviews with financial executives on the subject of business attitudes toward borrowing is used to develop the conceptual logic of the decision procedure, which is presented in terms of a mathematical programming formulation.